Chemotherapy alone may have equivalent survival as compared to suboptimal surgery in advanced endometrial cancer patients - Lisa Rauh; Jeanine N. Staples; Linda R. Duska (Elsevier, 2020)
Objective: To describe outcomes in patients with advanced endometrial cancer treated with chemotherapy only and compare them to patients treated with a combination of chemotherapy and surgery. Methods: Retrospective chart review for all patients diagnosed with stage III and IV endometrial cancer from January 1, 2000 to December 31, 2015. We abstracted relevant demographic and clinical data. Kaplan-Meier analysis was used to create survival curves; Cox proportional hazards regression model was used to identify prognostic factors. Results: Ninety-six patients met inclusion criteria; the median age was 64.5. Seventy patients were treated with combination therapy and 26 with chemotherapy alone. For the entire group, median overall survival (OS) was significantly different between groups (22.3 months surgery versus 9.8 months chemotherapy only, p = 0.0002). After multivariable analysis, having carcinosarcoma (HR 3.84 95% CI 2.64-5.03, p = 0.03), having grade 3 disease (HR 4.95 95% CI 3.70-6.18, p = 0.01), and having chemotherapy only (HR 4.13 95% CI 3.23-5.02, p = 0.002) were associated with increased mortality. When analysis was restricted to just patients who had a suboptimal debulking or chemotherapy alone, median OS was equivalent similar at 9.4 and 9.8 months (p = 0.46). Conclusion: For advanced endometrial cancer patients, surgery in addition to chemotherapy confers a survival advantage except when optimal debulking cannot be achieved.